2024
DOI: 10.2106/jbjs.23.01044
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Epidemiology of Hip Osteoarthritis in Japan

Taishi Sato,
Satoshi Yamate,
Takeshi Utsunomiya
et al.

Abstract: Background: The incidence of developmental dysplasia of the hip (DDH) in Japanese newborns has reduced drastically following a primary prevention campaign initiated around 1972 to 1973; this perinatal education campaign promoted maintaining the hips of newborns in the naturally flexed-leg position. The purpose of the present study was to describe the life course epidemiology of hip osteoarthritis (OA) in adolescent and adult patients and to assess its association with exposure to the primary preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A case-cohort study by Bruin et al [ 16 ] found that perioperative dosing of PPIs is associated with increased prosthetic joint infections. According to a multicenter, cross-sectional study conducted in 2022 in Japan, the mean age of new patients with hip osteoarthritis was 63.5 years [ 53 ], and those patients with osteoarthritis may undergo joint replacement surgery after taking NSAIDs for an extended duration [ 54 ]. However, infection and periprosthetic fractures are serious complications of joint replacement surgery [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case-cohort study by Bruin et al [ 16 ] found that perioperative dosing of PPIs is associated with increased prosthetic joint infections. According to a multicenter, cross-sectional study conducted in 2022 in Japan, the mean age of new patients with hip osteoarthritis was 63.5 years [ 53 ], and those patients with osteoarthritis may undergo joint replacement surgery after taking NSAIDs for an extended duration [ 54 ]. However, infection and periprosthetic fractures are serious complications of joint replacement surgery [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH), which includes DDH, hip subluxation, or hip dislocation, is a major disorder of hip pain and deformity. [ 1 3 ] Dysplastic acetabulum is characterized by a small diameter, defective bone structure, and proximalization of the femoral head. Femoral challenges include medullary canal stenosis, excessive anterior tilt, and high diaphragm-diaphragm angle with epiphyseal mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…conducted in 2022 in Japan, the mean age of new patients with hip osteoarthritis was 63.5 years [53], and those patients with osteoarthritis may undergo joint replacement surgery after taking NSAIDs for an extended duration [54]. However, infection and periprosthetic fractures are serious complications of joint replacement surgery [55].…”
Section: Plos Onementioning
confidence: 99%